Market share and efficiency: Causality test in Indonesian general insurance industry - Jamil, Iqram Ramadhan; Setiawan, Maman (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to analyze the relationship between market share and technical efficiency in the Indonesian general insurance industry. The data for the period 2010-2020 is used, which was obtained from the Indonesian Financial Services Authority (OJK). The results show that efficient companies emerged from the category of industry possessing comparatively higher and lower market shares. Furthermore, the panel Granger-causality test indicates a one-way direction of causality, where only the market share has an impact on the technical efficiency score. The panel regression using the Feasible Generalized Least Square (FGLS) model shows that market share has a negative impact on technical efficiency scores. Other variables, such as the age of the industry, merger, and acquisition are listed in the stock exchange and do not have a significant effect on the efficiency score. Based on the aforementioned findings, it can be inferred that the quiet-life hypothesis is applicable within the Indonesian general insurance sector. Consequently, the government must foster competition among the businesses operating within the industry.